2018
DOI: 10.1080/20008198.2018.1486123
|View full text |Cite
|
Sign up to set email alerts
|

Deployment-related trauma and post-traumatic stress disorder: does gender matter?

Abstract: Objective: Military research has attempted to identify whether women have an increased vulnerability to mental health issues following deployment-related trauma, but findings have been mixed. Most studies have controlled for childhood abuse, but not other non-deployment trauma (e.g. life-threatening illness), which may partly explain previous mixed results. This study assessed gender differences in the association between deployment-related trauma and post-traumatic stress disorder (PTSD) while controlling for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
0
13
0
2
Order By: Relevance
“…Due to lack of data on timing of non-deployment-related trauma, we were unable to include such events in our analysis. Exposure to non-deployment-related trauma is common among members of the military, and is likely related to both pre- and post-deployment mental health, particularly PTSD [49]. Our assessment and analysis of trauma exposure items had limitations: The eight items used to assess deployment-related trauma represent only a subset of a much larger set of potential events, though the reduced item set we used showed similar psychometric properties to a larger set.…”
Section: Discussionmentioning
confidence: 99%
“…Due to lack of data on timing of non-deployment-related trauma, we were unable to include such events in our analysis. Exposure to non-deployment-related trauma is common among members of the military, and is likely related to both pre- and post-deployment mental health, particularly PTSD [49]. Our assessment and analysis of trauma exposure items had limitations: The eight items used to assess deployment-related trauma represent only a subset of a much larger set of potential events, though the reduced item set we used showed similar psychometric properties to a larger set.…”
Section: Discussionmentioning
confidence: 99%
“…This result agrees with the findings of Khattak & Khattak (2014) and Nasar, Zulqarnain, Inayat, & Khan (2016), where no gender differences were also found on posttraumatic stress reactions among flood victims of Nowshera and Lahore respectively. Also, Frank et al (2018) found no gender differences. However, inconsistent results were established by Perkonigg, Kessler, Storz, & Wittchen (2000) and Solomonm, Gelkopf & Bleich (2005) who found a significant gender effect on posttraumatic reactions in their separate studies, where female victims reported higher reactions than their male counterpart.…”
Section: Discussionmentioning
confidence: 81%
“…Gender and education level of victims are among these factors. Most notably, gender has been explored as a potential predictor of increased PTSD following combat exposure; however, findings have been mixed (Frank et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Adult trauma included trauma types which first occurred at the age of 18 years or older. As data regarding deployment trauma were taken from the self-report questionnaire, we separated out trauma types unlikely to be deployment related, as per a previous study (Frank et al, 2018). These non-deployment-related traumas were further categorised as ‘Interpersonal’ (sexual assault, raped, stalked, beaten by spouse/romantic partner, badly beaten by anyone else) or ‘Non-interpersonal/other’ (unarmed civilian in a place of conflict, lived as a civilian in a place of ongoing terror, refugee, life-threatening automobile accident, child illness, life-threatening illness, someone close had traumatic experience).…”
Section: Methodsmentioning
confidence: 99%